Gender, Work and Migration Agency in Gendered Labour Settings (Taylor & Francis, 2018)
While the feminisation of transnational migrant labour is now a firmly ingrained feature of the contemporary global economy, the specific experiences and understandings of labour in a range of gendered sectors of global and regional labour markets still require comparative and ethnographic attention. This book adopts a particular focus on migrants employed in sectors of the economy that are typically regarded as marginal or precarious - domestic work and care work in private homes and institutional settings, cleaning work in hospitals, call centre labour, informal trade - with the goal of understanding the aspirations and mobilities of migrants and their families across generations in relation to questions of gender and labour. Bringing together rich, fieldwork-based case studies on the experiences of migrants from the Philippines, Bolivia, Ecuador, Zimbabwe, Mozambique, Mauritius, Brazil and India, among others, who live and work in countries within Europe, Asia, the Middle East and South America, Gender, Work and Migration goes beyond a unique focus on migration to explore the implications of gendered labour patterns for migrants' empowerment and experiences of social mobility and immobility, their transnational involvement, and wider familial and social relationships.
English
Keywords: Society & culture: general; gender; migration; work